1980
DOI: 10.1128/aac.18.5.730
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin-binding proteins of penicillin-susceptible and intrinsically resistant Neisseria gonorrhoeae

Abstract: The penicillin-binding proteins (PBPs) of Neisseria gonorrhoeae were investigated by using [3H]benzylpenicillin of high specific activity. This made it possible to label the PBPs both in cytoplasmic membranes and in the membranes of actively growing cells (in vivo labeling). A total of 20 strains isolated from different geographic locales showed the same pattern of three major PBPs, which had molecular weights of approximately 90,000, 63,000, and 48,000. Five clinical isolates of intrinsically penicillin-resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
97
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(98 citation statements)
references
References 34 publications
0
97
1
Order By: Relevance
“…They may be related to strain differences or, possibly, to differences in the degree of methicillin resistance. Multiple PBP alterations have only been seen at relatively high levels of resistance as reported for PBPs IN METHICILLIN-RESISTANT S. AUREUS 735 intrinsically penicillin-resistant pneumococci (25) and gonococci (5).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…They may be related to strain differences or, possibly, to differences in the degree of methicillin resistance. Multiple PBP alterations have only been seen at relatively high levels of resistance as reported for PBPs IN METHICILLIN-RESISTANT S. AUREUS 735 intrinsically penicillin-resistant pneumococci (25) and gonococci (5).…”
mentioning
confidence: 98%
“…The phenotypic loss of antibiotic resistance observable in MR cultures during growth at pH 5 Table 1 summarizes some of the relevant properties of the MR and MS strains used in our studies. MR strain RUCUS 1112 which was chosen for detailed study showed some, but not all, of the pleiotrophic properties described in the literature for other MR isolates of S. aureus (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These antibiotics inhibit cell growth by binding covalently to the active sites of essential PBPs (1,4). Although deactivation by beta-lactamase is the most common mechanism of resistance to these drugs (6), mutational alteration resulting in low affinity of target PBPs for beta-lactam antibiotics has been proposed as another mechanism of resistance to these drugs in some bacterial species (7)(8)(9), including strains of methicillin-resistant Staphylococcus aureus (MRSA) (10)(11)(12)(13). For some bacterial strains this mechanism may be sufficient to explain the resistance observed, but for strains of MRSA it cannot account for their unique property of heterogeneous resistance (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…,3-lactam antibiotics act by binding to and inactivating PBPs, disrupting balanced PBP activity and resulting in bacterial death. Clinically important antibiotic resistance may be due to the emergence ofPBPs with a lower affinity for f3-lactams (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%